Dealloyed AuNi Dendrite Anchored on a Functionalized Conducting Polymer for Improved Catalytic Oxygen Reduction and Hydrogen Peroxide Sensing in Living Cells. (2nd February 2016) - Naveen, Malenahalli Halappa; Gurudatt, Nanjanagudu Ganesh; Noh, Hui‐Bog; Shim, Yoon‐Bo
Abstract : Dealloyed‐AuNi dendrite anchored on carboxylic acid groups of a conducting polymer is prepared and demonstrated for the catalysis of the oxygen reduction reaction (ORR) and detection of hydrogen peroxide (H2 O2 ) released from living cells. The dendrite formation is initiated on a poly(benzoic acid‐2, 2′:5′, 2′′‐terthiophene) (pTBA) layer, where the polymer layer acts as a stable substrate to improve the long‐term stability and catalytic activity of the alloy electrode. A co‐deposition of Au and Ni is performed to produce a Ni‐rich Au surface at first; subsequent removal of the surface Ni atoms through electrochemical dealloying enhances the performance of the catalyst because of an increase in the electrochemically active area by 12 times. The hydrodynamic voltammetry of dealloyed‐AuNi@pTBA shows a half‐wave potential at –0.08 V, which is a large shift towards more positive potential when compared to those on AuNi@pTBA (−0.14 V) and commercial Pt/C (–0.12 V) electrodes. The proposed catalytic electrode achieved a superior analytical performance for the detection of trace H2 O2 (at –0.15 V) released from cancer and normal cells with a very low detection limit (ca. 5 nM). In addition, the in vitro studies suggest no significant cytotoxicity effect for the dealloyed sample and the viability of the cells are more than 85% even after 48 h of incubation. Abstract : A terthiophene polymer‐supported dealloyed AuNi dendrite (AuNi@pTBA) is designed by a simple electrochemical approach. This stable and active electrocatalyst is formed through complexation between the metal ions and the carboxylic acid groups of the polymer. Electrodes based on this material possess excellent catalytic properties, which surpass those of commercial Pt/C electrodes for the oxygen reduction reaction, and are good candidates for the sensitive detection of H2 O2 release from living cells.